1998
DOI: 10.1111/j.1600-0676.1998.tb00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of glycyrrhizin on NF‐κB binding activity in CC14‐ plus ethanol‐induced liver cirrhosis in rats

Abstract: Liver ISSN 0106-9543Inhbitory effect binding activitv J 4 . 0 " 4 e . liver cirrhosis in ; of glycyrrhizin on NF-KB in CC1,-plus ethanol-induced rats Wang J-Y, Guo J-S, Li H, Liu S-L, Zern MA. Inhibitory effect of glycyrrhizin on NF-KB binding activity in CC14-plus ethanol-induced liver cirrhosis in rats.Abstract: Aims/Background: Potenlini is an injectable compound whose active component is glycyrrhizin, which is extracted from licorice. Previous studies showed that it could reduce liver injury, improve alani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…NF-kB was found to be markedly activated which in turn regulates many of the inflammatory genes that are abnormally expressed in asthma [24,25]. Although GRZ has not been demonstrated to inhibit NF-kB binding in the airway or lung inflammation, however, it has been shown that it inhibited NF-kB binding activity in the rat liver cirrhosis model [26]. The recruitment of inflammatory cells from blood vessel to the airway needs various selectins and the blocking of these selectins has been demonstrated to inhibit antigen induced airway inflammation and late airway responsiveness in animal models [27,28].…”
Section: Discussionmentioning
confidence: 94%
“…NF-kB was found to be markedly activated which in turn regulates many of the inflammatory genes that are abnormally expressed in asthma [24,25]. Although GRZ has not been demonstrated to inhibit NF-kB binding in the airway or lung inflammation, however, it has been shown that it inhibited NF-kB binding activity in the rat liver cirrhosis model [26]. The recruitment of inflammatory cells from blood vessel to the airway needs various selectins and the blocking of these selectins has been demonstrated to inhibit antigen induced airway inflammation and late airway responsiveness in animal models [27,28].…”
Section: Discussionmentioning
confidence: 94%
“…It is known that the activation of NF-kappaB participates in Con A-induced hepatic iNOS expression [26]. GL has been reported to inhibit NF-KappaB binding activity in carbon tetrachloride and ethanol-induced chronic liver injury [32].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was reported that Ligusticum chuanxiong (L) exerted antiproliferative effects on PDGF-stimulated HSC-T6 cells, with modulation of cell cycle regulatory proteins conducive to apoptosis (Lin et al, 2006a). In the literature, glycyrrhizin, an active principle of licorice (Glycyrrhiza glabra, G), has been reported to abrogate ethanol-plus CCl 4 -induced hepatic fibrosis in rats, possibly by interfering with NFκB pathways (Wang et al, 1998). The present study showed that SLG could reduce hepatic mRNA expression levels of iNOS and ICAM-1 genes in fibrotic livers.…”
Section: Discussionmentioning
confidence: 99%
“…(L) on the proliferation of HSC-T6 cells have been reported (Lin et al, 2006a). Glycyrrhizin, an active compound of licorice (Glycyrrhiza glabra, G) has also been shown to abrogate hepatic fibrosis in rats (Wang et al, 1998). This study investigated whether a herbal extract combination, SLG, could exert antifibrotic effects on DMN-induced rat hepatic fibrosis.…”
Section: Introductionmentioning
confidence: 99%